Pengembangan Website Rumah Belajar Ceria Menggunakan Metode Web Modelling Language - Arsia Rini; Herlinda Kusmiati (Teknomatika, 2020)
Rumah Belajar Ceria (RBC) is a caring community in an effort to improve the quality of children's education and community empowerment, especially children and communities in disadvantaged areas and weak economies. RBC provides a program of activities for children and underprivileged communities at no charge. Previously, RBC had a website consisting of article, news and gallery pages. There was no admin page that processes the data of students and volunteers. So it is necessary to develop a RBC website that provides an admin page that can manage the website, and displays online registration to make it easier for people who want to register as volunteers (teachers) and students. RBC website development used Web Modelling Language (WebML) method. WebML is a high-level specification language that allows styles of both Entity Relationship or UML. The application of WebML is to design and implement data stored in a Database Management System (DBMS).